(untitled) (Biological Sciences - PJSIR, 2022)
The quality of water in dental units is of substantial importance since patients and dental staff are regularly exposed to water and aerosols generated during dental procedures. The aim of this study was to detect the bacterial contamination of dental unit water and investigate the effectiveness of the disinfectant. The biofilm of bacterial contaminant in dental unit waterlines was detected using bacterial culturing of heterotrophic bacteria, total coliforms and Pseudomonas aeruginosa. ln addition, presence of biofilm in dental unit waterlines was visualized using scanning electron microscopy (SEM). Subsequently, dental unit water lines were treated with disinfectant to eradicate bacterial contaminants from dental unit water lines and its effectiveness was tested after three months. This study showed that the bacterial contamination of the water samples ranged from not detected to 2.38 x 106 CFU/mL. Out of 34 DUWLs water samples tested the 30 (88.24%) samples exceeded the CDC/EPA recommended threshold of :¢S500 CFU/mL, whereas only 4 (11.76%) samples were able to meet the standards. Contamination by total coliforms and P. aeruginosa was detected in 52.94% and 64.7% of samples respectively. SEM displayed a dense biofilm on the lumen of tubing confirming the bacterial contamination. The intervention for disinfection of DUWLs resulted in more than 50% samples with acceptable bacterial count in follow up test performed after three months. The high rate of bacterial contamination of dental unit water highlights the need to disinfect and monitor the quality of DUWLs periodically and use a cleaner source of water.